Diseño de criterios de asignación para monitores de signos vitales en los servicios de hospitalización y urgencias del hospital universitario Mayor- Méderi (2019)
The development of this work focused on creating criteria for the assignment of monitoring teams, through the verification, evaluation and comparison of the capacity of vital signs monitors in the hospitalization and emergency services of the Hospital Universitario Mayor- Méderi.